BIOFILM MATRICES AS BIOMONITORING AGENT AND BIOSORBENT FOR CR(VI) POLLUTION IN AQUATIC ECOSYSTEMS - Andi Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
Heavy metal pollution in aquatic ecosystems has become one of the primary environmental problems. Cr(VI) is one of the most toxic and carcinogenic heavy metal pollutants. The degradation of aquatic ecosystems due to the Cr(VI) pollution usually occurs slowly, but the impact is accumulative. Hence, an awareness of the pollution often occurs when the impacts have already in the acute or chronic level. Therefore, the technologies to monitor and to solve the Cr(VI) pollution are critically important. The application of biological resources emerges as an alternative technology to solve the problems. This study analyzes the utilization of biofilm as a biomonitoring agent and a biosorbent to monitor and to immobilize Cr(VI) in the aquatic ecosystems, respectively. The development of the biofilm as a biomonitoring agent is conducted through the investigation of Cr(VI) concentration in the biofilm and the surrounding river water, while the utilization of the biofilm as a biosorbent is developed through the analysis of Cr(VI) adsorption characteristics to the biofilm. The results of this study reveal that the concentrations of Cr(VI) inside the biofilms are hundreds of times higher than the surrounding river water. The biofilms seem to accumulate the Cr(VI) from the surrounding river water through a physicochemical process. According to the result of this study, biofilms can become a promising biological agent to monitor and to immobilize Cr(VI) in the aquatic ecosystems.Keywords: Biofilm, Biomonitoring, Biosorption, Cr(VI), Water Pollution